Acquired Diplopia in Adults: Heavy Eye Syndrome. Issue 4 (2nd October 2022) - Pineles, Stacy L.
ABSTRACT: Heavy eye syndrome is a condition that results in an acquired, progressive strabismus that is due to extreme myopia and long axial length. The underlying pathogenesis of the condition is due to prolapse of the supero-temporal aspect of the myopic globe causing displacement of the lateral and superior rectus muscles inferiorly and nasally, respectively. Treatments for heavy eye syndrome often target this anatomical defect and seek to re-place the globe within the extraocular muscle cone. This review will discuss current theories of pathogenesis and treatment of heavy eye syndrome.